El régimen de alcaldías y veedurías en el concejo bajomedieval : el alcalde del alarifazgo en Jaén (Estudios de Historia de España, 2016)
In the final years of the Middle Ages we find in the Castilian municipalities a great abundance of offices, both of jurisdictional character and of inspector character (“alcaldes” and “veedores”, respectively), some of them had own and stable frame, while others were appearing and disappearing in agreement with the needs of the moment. We detain especially in the figure of the judge of the “alarifazgo” (masonry), manager of judging and executing in agreement with his competences in the area of the urbanism.
Keywords: Municipality; Jurisdiction; Judge; Inspector; Masonry